On estimate for numerical radius of some contractions - Karaev, M.T. (Український математичний журнал, 2006)
For the numerical radius of an arbitrary nilpotent operator T on a Hilbert space H, Haagerup and de la Harpe proved the inequality w(T)≤||T||cos(π/(n+1)), where n≥2 is the nilpotency order of the operator T. In the present paper, we prove a Haagerup-de la Harpe-type inequality for the numerical radius of contractions from more general classes.